1997
DOI: 10.1073/pnas.94.15.7959
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane/cytoplasmic domain-mediated membrane type 1-matrix metalloprotease docking to invadopodia is required for cell invasion

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
309
1
6

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(325 citation statements)
references
References 26 publications
9
309
1
6
Order By: Relevance
“…8), strongly suggesting that this type IV collagen-mediated pro-MMP-2 activation might represent a physiologically relevant system. This observation contrasts with the effect of ConA which, despite its high efficiency to promote pro-MMP-2 activation, failed to induce both degradation and invasion of the ECM [61].…”
Section: Type IV Collagen-mediated Mmp-2 Activation Is Associated Witcontrasting
confidence: 72%
See 2 more Smart Citations
“…8), strongly suggesting that this type IV collagen-mediated pro-MMP-2 activation might represent a physiologically relevant system. This observation contrasts with the effect of ConA which, despite its high efficiency to promote pro-MMP-2 activation, failed to induce both degradation and invasion of the ECM [61].…”
Section: Type IV Collagen-mediated Mmp-2 Activation Is Associated Witcontrasting
confidence: 72%
“…In this respect, it is interesting to note that even if both TPA and ConA treatments induced the formation of the 62-kDa intermediate MMP-2, only ConA efficiently converted this intermediate into the mature 59-kDa form, as previously reported by Gervasi and coworkers [56]. The ability of ConA to promote the second step of MMP-2 activation (i.e., the intermolecular autolytic cleavage) has been ascribed, at least in part, to its potential to cluster membrane glycoproteins, including MT1-MMP, thereby favoring the autoproteolytic processing of adjacent MT1-MMP-associated intermediate MMP-2 species [56,60,61].…”
Section: Mmp-2 Activation By Tpa-and Cona-treated Ht1080 Cellsmentioning
confidence: 55%
See 1 more Smart Citation
“…In tissues from 41 patients with bladder cancer, using nonquantitative RT -PCR, MT1-MMP was shown to associate strongly with decreased survival (Kanayama et al, 1998). Nakahara et al (1997) observed the preferential localisation and functional significance of MT1-MMP in the invadopodia of melanoma cells. Localisation studies suggest that stromally derived MT1-MMP may be cleaved from the cell surface and that the resulting soluble protein is endocytosed and re-expressed by the tumour cells (Chenard et al, 1999), but this is currently unsubstantiated.…”
Section: Discussionmentioning
confidence: 90%
“…A complex of TIMP2 and MT1-MMP is now known to be a receptor and activator of MMP2. 3 MMP1, MMP2, MMP3, MMP7, MMP9, MMP11, MMP13, MT1-MMP, TIMP1, and TIMP2 have been detected in various histological types of lung carcinomas. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, previous studies rarely examined noninvasive carcinomas, and little is known about how MMP expression differs in noninvasive and invasive carcinomas.…”
mentioning
confidence: 99%